MENINGKATKAN KOMPETENSI GURU DALAM PEMBUATAN BAHAN AJAR BERBASIS TEKNOLOGI INFORMASI DI SMA NEGERI 2 PLAYEN GUNUNG KIDUL - Muhammad Sholeh; Prita Haryani (JURNAL GAUNG INFORMATIKA, 2018)
The use of information and communication technology (ICT) in teaching and learning process (PBM) is currently one of the alternatives in the learning process.ICT-based teaching materials are becoming more interactive means of explaining a material. With ICT developed learning materials equipped with multimedia facilities, sothat its presentation can be more interesting and the material can be depicted visually so that the presentation of the material can be equipped with pictures, video andanimation,As an effort to improve the competence of teachers in developing ICT-based teaching materials, in SMA Negeri 2 Playen Gunung Kidul organized training and assistance in making teaching materials. The material provided is to create teaching materials using the Video Scribe app. The Scribe Video application can be used tocreate teaching materials and comes with multimedia as well as more interactive and easy development